Desain dan Analisis Pembangkit Tegangan DC Tinggi Tiga Tahap dengan Metode Crocroft - Walton - Setiyono (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
High DC voltage sources are required in a variety of applications including nuclear measurements, medical equipment (X-rays), corona testers, dielectric strength testing, pulse voltage generation and high voltage electrical resistance testing. Various methods have been developed to produce high DC voltage, including DC-DC converters, boost converters, flyback transformers and Crocroft - Walton. This paper describes a high DC voltage generator using the Crocroft-Walton (CW) rectifier method. This method is based on the principle of converting a low voltage AC wave to a high DC voltage (converter), the level of which is many times the input voltage. The aim of this research is to develop a design for a 12 V DC voltage multiplier to a high DC voltage without a voltage step-up transformer using the CW method using Matlab Simulink tools. The switching control strategy uses two high frequency and low frequency components in the converter circuit. The simulation results show that the input voltage value was successfully doubled to approximately six times, with the highest output voltage value being 4973 V at a pulse width (duty cycle) setting of 0.99 on the converter circuit switch.